2015
DOI: 10.2147/copd.s96412
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-induced lung inflammation in COPD mediated via LTB4/BLT1/SOCS1 pathway

Abstract: BackgroundEvidence suggests that suppressor of cytokine signaling 1 (SOCS1) is crucial for the negative regulation of inflammation. We investigated the relationship between smoking, SOCS1, and leukotriene B4 (LTB4) in vitro and in clinical samples of COPD; besides which we detected the impact of LTB4 receptor 1 (BLT1) antagonist on inflammation.MethodsSOCS1 expression in bronchial mucosa was determined by immunohistochemistry and real-time polymerase chain reaction. We also detect SOCS1 and BLT1 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Springer observed a transcriptional down-regulation of SOCS3 in COPD patients [38]. Dong et al proved that SOCS1 expression was significantly decreased in the lung tissues from COPD patients [39]. In our studies, we also found a significant reduction of SOCS1 and SOCS3 expression in COPD rats and CSE+LPS-induced cells.…”
Section: Discussionsupporting
confidence: 80%
“…Springer observed a transcriptional down-regulation of SOCS3 in COPD patients [38]. Dong et al proved that SOCS1 expression was significantly decreased in the lung tissues from COPD patients [39]. In our studies, we also found a significant reduction of SOCS1 and SOCS3 expression in COPD rats and CSE+LPS-induced cells.…”
Section: Discussionsupporting
confidence: 80%
“…Further, the release of SOCS1-containing vesicles was significantly reduced in smokers compared with non-smokers [ 73 ], which suggests that impaired activity of SOCS1 may contribute to the inflammatory responses that are associated with tobacco smoke exposure. Moreover, the expression of IL-6 and TNF-α were negatively correlated with the expression of SOCS1 in macrophages upon cigarette smoke exposure [ 74 ].These findings suggests that exosomes can be used as a mediators to target cytokine signaling pathways in case of smoking-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory disease of the airway. The pathology of COPD is characterized by neutrophilic airway inflammation, airway remodeling, and pulmonary emphysema in response to cigarette smoke (CS) exposure ( Dong et al, 2015 ; Jung et al, 2016a ). CS is a complex mixture of oxidant radicals and various chemical compounds, including reactive aldehydes and semiquinones.…”
Section: Introductionmentioning
confidence: 99%